Short Communication: The isolation of Klebsiella variicola’s cellulase from Macrotermes gilvus gut in Indralaya Peatlands, Indonesia - DWITA OKTIARNI; HERMANSYAH HERMANSYAH; EDDY IBRAHIM; MARSI MARSI; HASANUDIN HASANUDIN; MIKSUSANTI MIKSUSANTI; DEDE HERI YULI YANTO; NANIK RAHMANI; GETARI KASMIARTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Oktiarni D, Hermansyah, Ibrahim E, Marsi, Hasanudin, Miksusanti, Yanto DHY, Rahmani N, Kasmiarti G. 2023. Short Communication: The isolation of Klebsiella variicola’s cellulase from Macrotermes gilvus gut in Indralaya Peatlands, Indonesia. Biodiversitas 24: 4218-4222. Termites are organisms that can inflict damage on agricultural, forest, and furniture materials. Furthermore, they can positively affect the ecosystem due to their ability to break down lignocellulose-containing materials. According to previous findings, the cellulolytic bacteria from the termite Macrotermes gilvus gut obtained in Indralaya Peatlands showed activity and hydrolyzed cellulose in a CMC agar medium. In this study, the cellulase enzymes of Klebsiella variicola isolated from Macrotermes gilvus gut showed higher cellulolytic indexes after staining with Congo red. Furthermore, the enzyme was purified and characterized using ammonium sulfate precipitation and dialysis. SDS PAGE and zymogram analysis reported a molecular mass of 20 kDa, with optimal activity at pH of 6 and temperature of 50°C.